Aplikasi Beberapa Jenis Dan Dosis Mikroorganisme Lokal Limbah Tomat Dan Sayuran Dalam Meningkatkan Pertumbuhan Dan Hasil Tanaman Cabai (Capsicum Annum L.) - Panjaitan, Fany Juliarti; Lele, Onesimus Ke; Taopan, Rizki Adiputra; Kurniawan, Yohanes (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
Go organic in 2010 is a program launched by the government to produce organic agricultural products. The organic red chili plant is one of the products of the go organic program in 2010 which has high economic value, so it is necessary to increase the red chili plant the productivity. The use of local microorganisms can be used as an alternative in producing organic chili products. This study aims to determine the effect of type and dose of the best local microorganism on the growth and yield of chili. The study used a factorial randomized block design consisting of two factors. The first factor was local microorganisms (P) type consisting of 3 levels: P1(vegetables), P2(tomatoes), and P3(vegetables and tomatoes), the second factor was local microorganisms (D) dose consisting of 5 levels: D0: 0 cc/L of water, D1: 25 cc/L, D2: 50 cc/L, D3: 75 cc/L, D4: 100 cc/L. The results showed that P3D1 is the best treatment in increasing plant height, flowers number and accelerating 80% flowering age. Treatment of MOL P1 type and 25 cc/L dose is the best treatment in increasing the chili plants diameter. P3D4 is the best treatment in increasing the chilies wet weight per plant.